Synthesis and Crystal Structure of tris-(1,10-Phenanthroline)-Iron(II) Dichromate Tetrahydrate, Fe(C12H8N2)3Cr2O7·4H2O - Liu, Hai-Xing; Jian, Fang-Fang; Wang, Jing; Yu, Zhang-Xue; Zhang, Qing-Hua; Tai, Xi-Shi (Asian Journal of Chemistry, 2013)
In this report, Fe(C12H8N2)3Cr2O7·4H2O, was prepared by the reaction of FeCl2, 1,10-phenanthroline and potassium chromate. The asymmetric unit is composed of a [Fe(phen)3]2+ cation, a Cr2O72- anion and four water molecules. The metal centre is coordinated in a distorted octahedral mode by six N atoms from three 1,10-phenanthroline. The Cr2O72- anion is in a staggered conformation. The crystal packing is stabilized by intermolecular O-H...O and O-H...N hydrogen bonds and p-p interaction.